(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses modern aspects of effective organization of public administration in the Federal Republic of Germany. Improving governance and effective governance have always been important in the world. In developed countries, we can see that due to the efficiency, effectiveness and transparency of public administration, budget funds are spent wisely, corruption is low, bureaucratic barriers are reduced, and the relationship between citizens and government agencies is systematic.